The presence of gastrointestinal symptoms and weight loss as risk factors for malnutrition in patients with gastric cancer undergoing chemotherapy (Research, Society and Development, 2023)
Introduction: Gastric Cancer (GC) is the fifth most common cancer in the world and the third most common cause of cancer-related death. The treatment is multimodal, among the therapies used is chemotherapy, which can cause symptoms such as nausea and vomiting, interfering with the patient's nutritional status. Objective: To assess whether the presence of gastrointestinal symptoms and weight loss represent risk factors for malnutrition in patients with gastric cancer undergoing chemotherapy. Methodology: Cross-sectional descriptive and analytical study, with non-probabilistic convenience sampling. Carried out with patients diagnosed with gastric cancer, adults and elderly of both genders, from January 2020 to December 2022. For statistical analysis, correlation, association and regression tests were used, adopting a 5% significance level. Results: Thirty patients were evaluated, 40.0% had malnutrition according to BMI, 53.3% had weight loss and 46.6% had gastrointestinal symptoms, with nausea and loss of appetite being more prevalent. Conclusion: Although the presence of gastrointestinal symptoms and the occurrence of weight loss was not considered a risk factor according to the regression test, the attention and proper management of the multidisciplinary team is crucial to avoid the occurrence of these aggravating factors and intervene assertively to promote improvement. nutritional status, functional capacity and quality of life of these patients.